Effective Implementation of Teaching Skills and Religious Activities to Enhance the Quality of Learning In Islamic Religious Education at MTsN 2 Surabaya - Yulianto, Agus; Darmawan, Didit (EDUCAN : JURNAL PENDIDIKAN ISLAM, 2024)
The quality of Islamic Religious Education teaching is influenced by the understanding and application of Islamic teachings in everyday life. For this reason, this study aims to analyse the influence of teachers' basic teaching skills and students' religious practices on Islamic Religious Education learning outcomes at State Tsanawiyah Madrasah 2 Surabaya City. Islamic Religious Education plays an important role in shaping students' character and morals, so that the quality of Islamic Religious Education teaching is a crucial factor in achieving the goals of religious education. The factors studied include teachers' basic teaching skills and students' religious practices. This research used a quantitative approach with a sample of 100 class VII students. Data was collected through questionnaires and regression analysis was used to assess the influence of independent variables on Islamic Religious Education learning outcomes. Research findings show that teachers' basic teaching skills and students' religious practices partially and simultaneously have a positive effect on Islamic Religious Education learning outcomes. These results indicate that teachers' basic teaching skills which involve the ability to convey material clearly, mastery of teaching methods, and adaptability to students' needs have a positive impact on students' understanding of religious teachings. In addition, students' religious practices from religious activities, such as prayer, reading the Koran, and other religious practices, contribute positively to Islamic religious education learning outcomes